Comprehensive structural characterization of chromium-doped zinc oxides - Ates, Tankut; Keser, Serhat; Bulut, Niyazi; Kaygili, Omer (Springer-Verlag Italia Srl, 2025)
This study presents a comprehensive investigation of the effects of chromium (Cr) on the structural properties of zinc oxide (ZnO). X-ray diffraction (XRD) analysis confirmed the formation of the ZnO wurtzite phase for all samples. At lower Cr concentrations (up to 1.4 at%), Cr3(+) ions were successfully incorporated into the ZnO lattice without forming secondary phases, indicating effective substitutional doping. However, at higher Cr contents (>= 2.8 at%), the formation of a secondary ZnCr2O4 spinel phase was observed, suggesting that the Cr solubility limit in ZnO was exceeded. Cr content influenced various crystal-structure-related parameters such as crystallinity, crystallite size, lattice parameters, Zn-O bond length, lattice strain, and stress. The texture coefficient (TC(hkl)) analyses revealed a shift in preferential growth orientation from the (200) plane to the (004) plane with increasing Cr concentration. FTIR spectra supported the presence of Zn-O vibrational modes and changes in surface chemistry, while SEM images showed morphology evolution and increased surface complexity with doping.
Keywords: X-ray diffraction (XRD); Zinc oxide (ZnO); Morphology; Chromium doping